Effects of Adding Morphine to Periarticular Infiltration Analgesia Combined with Single Dose Epidural Morphine in Total Knee Arthroplasty: A Randomized Controlled Study. Issue 4 (15th February 2023) - Li, Yicheng; Wulamu, Wuhuzi; Yushan, Nuerailijiang; Guo, Xiaobin; Gu, Wenchao; Cao, Li; Zhang, Xiaogang
Abstract : Objective: Morphine plays an important role in postoperative analgesia after total knee arthroplasty (TKA). However, there are limited data that investigate the administration ways of morphine. To evaluate the efficacy and safety of adding morphine to periarticular infiltration analgesia (PIA) combined with single‐dose epidural morphine for the patients undergoing TKA. Methods: In total, 120 patients with knee osteoarthritis who underwent the primary TKA from April 2021 and March 2022 were randomized into three groups (a cocktail containing morphine with single‐dose epidural morphine [Group A]; a cocktail containing morphine [Group B]; and a cocktail free of morphine [Group C]). The three groups were compared based on the Visual Analog Score at rest and during motion, requirement of tramadol, functional recovery including quadriceps strength and range of motion, and adverse events including nausea and vomiting and local and systemic adverse events. The repetitive measure analysis of variance and chi‐square test among three groups were used to analyze the results. Results: Analgesia strategy in Group A (0.4 ± 0.8, and 0.9 ± 1.0 points, respectively) significantly reduced rest pain at 6 and 12 h after surgery relative to Group B (1.6 ± 1.2, and 2.2 ± 1.4 points, respectively) ( p  < 0.001), and the analgesic effect of Group B was stronger than that of Group C (2.1 ± 0.9, and 2.6 ± 0.9 points, respectively) ( p  < 0.05). Rest pain at 24 h after surgery was significantly lower in Group A (2.5 ± 0.8 points) and B (1.9 ± 1.0 points) than in Group C (2.5 ± 0.8) ( p  < 0.05). Within 24 h after surgery, the requirements for tramadol in Group A (0.25 g) and Group B (0.35 g) were significantly lower than those in Group C (0.75 g) ( p  < 0.05). Within 4 days of surgery, the quadriceps strength in the three groups increased gradually, and no statistical significance was noted among the three groups ( p  > 0.05). From the second day to the fourth day after surgery, although the three groups showed no statistical difference in the range of motion, the result of Group C was inferior to that of the other two groups. There were no significant differences in the incidence of postoperative nausea and vomiting and metoclopramide consumption among the three groups ( p  > 0.05). Conclusion: PIA combined with single‐dose epidural morphine effectively reduces early postoperative pain and tramadol requirement as well as few complications, which can become a safe and effective measure to improve postoperative pain after TKA. Abstract : After preparation of the bony surfaces, the multimodal cocktail is injected into the posterior capsule and iliotibial band, and then the medial and lateral collateral ligaments and meniscal bed are infiltrated with the multimodal cocktail. After the implantation of posterior stabilized prosthesis in all patients, the quadriceps, retinaculum, and patellar tendon are infiltrated with the multimodal cocktail.